The Growth Performance of Kappaphycus alvarezii Cultivated in a Lead (Pb) Contaminated Farming Area (Agrikan Jurnal Agribisnis Perikanan, 2024)
Decreasing seaweed aquaculture in Panjang Island was allegedly affected by deterioration of water quality after the expansion of industry in Banten Bay. Thus, it is important to evaluate the growth performance of Kappaphycus alvarezii in the lead-contaminated farming area. The study took place in Panjang Island and Lontar waters to compare the growth performance of K. alvarezii in a high and low lead-exposes farming area. The seaweed farmed for 30 days by using a long-line method. Water samples collected four times with an interval of 10 days. Specific growth rate, temperature, pH, salinity, water motion, Secchi depth, and depth of the water were the parameter measured. The results show a high lead concentration in Panjang Island with the value of 0.024-0.046 mg/L, while in Lontar waters, the concentration was 0.020-0.026 mg/L. Even though Panjang Island has higher lead concentrations, but the weight growth of the seaweed from Panjang Island was higher than the seaweed from Lontar waters with the seaweed weight of 439.92 g compared to 239.13 g, respectively. The growth performance of K. alvarezii was not affected by the pollution when other environmental factors were suitable for the growth of this seaweed. Higher growth performance of K. alvarezii in high polluted area was supported by suitable other environmental factorsLoA, Kor
Keywords: Kappaphycus alvarezii; lead; Lontar; Panjang Island; pollution